Simulasi Keamanan Jaringan pada DPDK OpenvSwitch Berbasis Network-Based Intrusion Detection System (NIDS) - Juan Tamalaki Ohyver; Dian W. Chandra (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2023)
Virtual networks in a virtualized server environment use Virtual Switches to interconnect network traffic on the Virtual Machine with the physical network. However, at this time attacks carried out by hackers often occur in physical and virtual server environments. Hacking on computer network security is often done by a group of people who want to penetrate the security of a system. This activity aims to find, obtain, change, and even delete information. Therefore the use of OpenvSwitch and the application of NIDS in it is very useful for virtual network security. In this study, a simulation was carried out to find out how big the percentage of NIDS success was in detecting DOS attacks directed at OpenvSwitch. From the results of this study, the percentage of success for Snort in detecting attacks in this test is around ± 75%.